Influence of SAS software on the learning of statistics at the university level - Uribe Hernández, Yrene Cecilia (2023)
This article examines the use of the SAS tool in the learning of statistics. the type of research was applied with a quasi-experimental design and quantitative approach, the sample was determined by a non-probabilistic method comprising 28 students for both groups; for the collection of information, a pre-test and a post-test were applied, validated with expert judgment and V. Aiken, its reliability with the Spearman Brown coefficient. After the experiment, the results showed higher averages in favor of the experimental group to whom the SAS software was applied in its statistical learning dimensions at a descriptive and inferential level. In order to know the distribution of the data, the Shapiro Wilk numerical method was used, the result of the test gave the certainty to choose the TStudent test for two independent samples at 95% with a level of confidence and 0.05 significance. It is concluded that the SAS software improves the levels of learning of statistics, increases their creativity, they feel more motivated, and there is an interaction favoring more active learning.